Smc5/6 As A Novel Modulator Of Hepatitis B Virus Infection (Applied Biological Research, 2017)
The Smc5/6 protein complex inhibits the replication of hepatitis B virus  (HBV) by an unknown mechanism. HBx, the regulatory protein of HBV, binds Smc5/6, promotes its ubiquitination by recruiting it to DDB1-CRL4  E3 ubiquitin ligase and mediates proteasomal degradation. In absence of  HBx, Smc5/6 complex binds to cccDNA of HBV and inhibits transcription  and replication of HBV. Thus Smc5/6 complex acts antagonistically to HBV  infection. This could aid in the development of potential therapeutics against  HBV infection. In this minireview, the role of Smc5/6 in replication and its  interaction with HBx protein of HBV is discussed.
Keywords: HBV; Smc5/6 complex; DDB1; maintenance of chromoosmes; Hepatitis B virus; HBx; HBV protein X; CRL4; CUL4- ROC1 ligase; DDB1 DNA damage binding protein1